2003
DOI: 10.1128/jvi.77.18.9780-9789.2003
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Swine Vesicular Disease Virus: Mapping of Changes Occurring during Adaptation of Human Coxsackie B5 Virus To Infect Swine

Abstract: The structure of swine vesicular disease virus (SVDV) was solved and refined at a 3.0-Å resolution by X-ray crystallography to gain information about the role of sequence changes that occurred as this virus evolved from the parental human pathogen coxsackievirus B5 (CVB5). These amino acid substitutions can be clustered in five distinct regions: (i) the antigenic sites, (ii) the hydrophobic pocket of the VP1 ␤-sandwich, (iii) the putative CAR binding site, (iv) the putative heparan sulfate binding site, and (v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 56 publications
1
18
0
2
Order By: Relevance
“…The amino acid substitutions found in SVDV variants lacking the heparinbinding phenotype were initially mapped using an SVDV homology model (Jiménez-Clavero et al, 2000). The crystal structure of SVDV recently determined (Jiménez-Clavero et al, 2003;Verdaguer et al, 2003) confirmed the location of these amino acid substitutions.…”
Section: Methodsmentioning
confidence: 51%
See 1 more Smart Citation
“…The amino acid substitutions found in SVDV variants lacking the heparinbinding phenotype were initially mapped using an SVDV homology model (Jiménez-Clavero et al, 2000). The crystal structure of SVDV recently determined (Jiménez-Clavero et al, 2003;Verdaguer et al, 2003) confirmed the location of these amino acid substitutions.…”
Section: Methodsmentioning
confidence: 51%
“…The crystal structure of FMDV serotype O in complex with HS (Fry et al, 1999) showed the HS binding site of the virus in a depression of positive electrostatic charge on the capsid, contributed by the three surface proteins: VP1, VP2 and VP3. The predicted HS binding for SVDV maps near, but does not overlap, the FMDV HS binding site (Fry et al, 1999;Verdaguer et al, 2003). Among the two amino acid substitutions that seem to be involved in the HS binding site, position 1266 is relatively variable among other SVDV variants.…”
Section: Discussionmentioning
confidence: 99%
“…These changes occurred along the backbone or the secondary branches of the CVB5 phylogeny, and they determined the evolutionary pathway of lineages. The structural features indicated were reported for other enteroviruses, in particular, swine vesicular disease virus (SVDV) and coxsackievirus B3 (CVB3), as described earlier (52,53,54). ϩ, amino acid positions exposed at the virion surface (see also figure 4B); Ag, antigenic.…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…The evolution of genogroup B was shaped by changes selected at three residues within or near antigenic site 3A (G273S, D276E, and T279A). Antigenic site 1 is located within the B-C loop of VP1, a structure exposed near the 5-fold axis of the EV particles (6,52,54). Antigenic site 3A is made up of residues within the VP1 C terminus, which is located on the virus top surface.…”
Section: Phylogenetic Clustering Of Cvb5 Taxa In the 1dmentioning
confidence: 99%
“…The crystallographic information from CVB3 (PDB accession number 1COV) (64) and SVDV (PDB accession numbers 1OOP and 1MQT) (31,101) as well as the footprints of CAR (39) and DAF (36) on the surface of CVB3 were used. The numbering of amino acids is according to the residue positions in the CVB5 sequence.…”
Section: Phylogenetic Relationships Of Cvb5 Virusesmentioning
confidence: 99%